Experimental solar water thermolysis - Baykara, SZ (PERGAMON-ELSEVIER SCIENCE LTD, 2004)
Water thermolysis and various experimental techniques for hydrogen production by solar water thermolysis are briefly discussed and their performance levels are compared. Some results, obtained over a period of time, at the solar furnace site in Montreal, Canada are presented. Two main process types are considered here. One in which either hydrogen or oxygen is separated from the reacting gas mixture directly at reaction temperature, the other in which hydrogen is isolated after the product gas is quenched to a much lower temperature. Though processes with effusional separation of hydrogen at reaction temperature are expected to be more energy conserving, conversion rates in all processes are still quite low due to material related limitations, since thermolysis favours high temperatures exceeding 2000 K. In practice, maximum tolerable temperature in the reactor is 2500 K. Under such operating conditions catalysis is hardly an option. New reactor designs, operation schemes and materials are needed for new breakthrough in this field. Some possibilities regarding these topics are discussed. (C) 2004 International Association for Hydrogen Energy. Published by Elsevier Ltd. All rights reserved.
Keywords: water thermolysis; experimental water thermolysis; solar water thermolysis; hydrogen production from water; DIRECT THERMAL-DECOMPOSITION; REACTIONS INVOLVING HYDROGEN; ON-SITE SEPARATION; GAS-PHASE; MEMBRANE; ENERGY; OXYGEN; FEASIBILITY; REACTORS; PRODUCTS; Chemistry; Electrochemistry; Energy & Fuels